2020
DOI: 10.36849/jdd.2020.4913
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Utilization of Dermatologists for Primary Cicatricial Alopecias

Abstract: This document contains proprietary information, images and marks of Journal of Drugs in Dermatology (JDD). No reproduction or use of any portion of the contents of these materials may be made without the express written consent of JDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Some studies have shown differences in clinical trial enrollment for and disease presentation of alopecia areata, toxic exposure to chemicals in hair products, physical activity due to hair styling, advocacy efforts, and utilization of dermatologists for cicatricial alopecias. [11][12][13][14][15][16] Given that underrespresented in medicne residents tended to feel more comfortable managing specific hair conditions, the true level of resident comfort with managing these conditions may actually be overestimated as they represented 24% of participants. Even though 45.5% of participants reported having a hair-specific clinic, the majority of responses from this group showed no differences in comfort level treating diseases like CCCA, TA, and TN.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown differences in clinical trial enrollment for and disease presentation of alopecia areata, toxic exposure to chemicals in hair products, physical activity due to hair styling, advocacy efforts, and utilization of dermatologists for cicatricial alopecias. [11][12][13][14][15][16] Given that underrespresented in medicne residents tended to feel more comfortable managing specific hair conditions, the true level of resident comfort with managing these conditions may actually be overestimated as they represented 24% of participants. Even though 45.5% of participants reported having a hair-specific clinic, the majority of responses from this group showed no differences in comfort level treating diseases like CCCA, TA, and TN.…”
Section: Discussionmentioning
confidence: 99%